Visible and Red Light-Triggered Anticancer Profile of a Ferrocene-Re(I)-Tricarbonyl Conjugate: Experimental and Theoretical Studies - Kushwaha R.; Upadhyay A.; Peters S.; Yadav A.K.; Mishra A.; Bera A.; Sadhukhan T.; Banerjee S. (My University, 2025)
We have red-shifted the light absorbance property of a Re(I)-tricarbonyl complex via distant conjugation of a ferrocene moiety and developed a novel complex ReFctp, [Re(Fctp)(CO)3Cl], where Fctp = 4′-ferrocenyl-2,2′:6′,2″-terpyridine. ReFctp showed green to red light absorption ability and blue emission, indicating its potential for photodynamic therapy (PDT) application. The conjugation of ferrocene introduced ferrocene-based transitions, which lie at a higher wavelength within the PDT therapeutic window. The time-dependent density functional theory and excited state calculations revealed an efficient intersystem crossing for ReFctp, which is helpful for PDT. ReFctp elicited both PDT type I and type II pathways for reactive oxygen species (ROS) generation and facilitated NADH (1,4-dihydro-nicotinamide adenine dinucleotide) oxidation upon exposure to visible light. Importantly, ReFctp showed effective penetration through the layers of clinically relevant 3D multicellular tumor spheroids and localized primarily in mitochondria (Pearson’s correlation coefficient, PCC = 0.65) of A549 cancer cells. ReFctp produced more than 20 times higher phototoxicity (IC50 ∼1.5 μM) by inducing ROS generation and altering mitochondrial membrane potential in A549 cancer cells than the nonferrocene analogue Retp, [Re(CO)3(tp)Cl], where tp = 2,2′:6′,2″-terpyridine. ReFctp induced apoptotic mode of cell death with a notable photocytotoxicity index (PI, PI = IC50dark/IC50light) and selectivity index (SI, SI = normal cell’s IC50dark/cancer cell’s IC50light) in the range of 25-33. © 2024 American Chemical Society